Marked Hypoleptinemia Precedes Overt Fat Loss in Immune Checkpoint Inhibitor-induced Acquired Generalized Lipodystrophy. Issue 2 (9th March 2023) - Dhanasekaran, Maheswaran; Sandooja, Rashi; Higgins, Alexandra S; Simha, Vinaya
Abstract: Immune checkpoint inhibitors (ICIs) targeting cancer cells that evade immune T-cell regulation have revolutionized the treatment of metastatic carcinomas. Unfortunately, secondary endocrinopathies associated with ICI, including adrenal insufficiency, primary hypothyroidism, autoimmune diabetes, and rarely hypoparathyroidism, are increasing. Lipodystrophy, presumably due to the autoimmune destruction of adipocytes, leading to metabolic complications, is a less recognized adverse effect of ICI therapy. We present a case of a 66-year-old Caucasian woman treated with pembrolizumab, an anti-programmed death 1 inhibitor, for metastatic lung adenocarcinoma. Fifteen months after the treatment initiation, she was found to have hyperglycemia, hyperlipidemia, and hepatic steatosis but without any evidence of autoimmune diabetes. She was also noted to have isolated buccal fat pad loss, raising suspicion of acquired lipodystrophy. Despite well-preserved subcutaneous fat over the trunk and limbs, she had undetectable serum leptin levels. Whole-body fluorodeoxyglucose (FDG)-positron emission tomography scan showed diffuse mild FDG activity throughout the subcutaneous tissue, suggesting underlying inflammation. Over the next 3 months, she developed progressive fat loss leading to generalized lipodystrophy. Adipose tissue dysfunction, secondary to ICI-induced subclinical panniculitis, precedes overt fat loss and is characterized by hypoleptinemia and metabolic abnormalities.